Attractiveness of Non-metropolitan Cities - Tkacheva, Marina (project baikal, 2017)
The discussion focuses on the peculiarities of non-metropolitan cities that attract their citizens. Different alternatives of formation of urban identity and uniqueness are proposed. The proposals for the creation of urban identity in Irkutsk are analyzed. The discussion features the connection between the historical development of the city and its present-day problems: development of the Angara waterfront; preservation of wooden architecture and V. Pavlov’s architectural heritage. It brings up an issue of distinctness of city mythology.
Keywords: architecture; city; identity; uniqueness; Irkutsk; Angara; Vladimir Pavlov; wooden architecture; neo-brutalism; city mythology